X-Ray holographic imaging of hydrated biological cells in solution - Matthias Bartels and Martin Krenkel and J. Haber and Robin Niklas Wilke and Tim Salditt (Physical Review Letters, 2015)
We demonstrate nanoscale x-ray holographic imaging using optimized illumination wave fronts emitted by x-ray waveguide channels. Mode filtering minimizes wave-front distortions and artifacts encountered in most hard x-ray focusing schemes, enabling quantitative reconstruction of the projected density, as evidenced by a test pattern imaged with a field of view of about 20×40  μm and at 22 nm resolution. The dose efficiency and contrast sensitivity make the optical scheme compatible with samples of intrinsically low contrast, typical for hydrated soft matter. This is demonstrated by imaging bacteria in the hydrated and living state, with quantitative phase contrast revealing dense structures of the bacterial nucleoids associated with compactified DNA. In response to continued irradiation, characteristic changes in these dense structures are observed.